STATE AND FURTHER DEVELOPMENT OF BUSINESS STRUCTURES IN WAR CONDITIONS - BOKOVETS, Viktoriіa; GEVCHUK, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the issue of losses during the Russian military invasion of Ukrainian business. The activity in modern conditions of business structures is analyzed. The state and trends of the impact of military events on the economic situation in the country have been studied, in particular, the socio-economic losses that Ukraine suffers from Russia's invasion of our territory have been determined. During the war, Ukrainian business lost more than two years in the COVID-19 pandemic. The extent of the damage and the long-term consequences are difficult to estimate, as hostilities continue across the country.According to the National Bank, during the war, Ukraine's economy lost 50% of "unproduced" GDP. That is, every week the national economy costs more than 50 billion hryvnias. And it is without losses from destruction. Many businesses found themselves in areas of active hostilities and were forced to evacuate to safer regions or stop working. However, even those businesses that are relatively far from shelling suffer from logistics problems and shortages of raw materials. The IMF estimates Ukraine's losses due to the military invasion of the Russian occupiers at 35 percent of GDP. Only 17% of companies work in full, and every third does not work. One third of entrepreneurs plan to resume operations. Surveys of other organizations showed approximately the same results.It is noted that Russia started a full-scale war with Ukraine at the beginning of the spring sowing campaign of 2022. This was also done to provoke a crisis in the country, panic, food shortages, and later famine. Especially since the food crisis will not be limited to the borders of our country, but will affect the world food market. It is stated that the state should first of all support producers of products and medicines, pharmacies, agrarians (especially during the sowing period), as well as light industry. Help all businesses, but these areas are important for the survival of the country right now. It is pointed out that it is necessary to relocate, preserve (and partially provide) jobs and thus ensure its own solvency, the solvency of the population and ensure revenues to the state budget. The main directions of revival of the activity of the enterprises in today's languages are outlined.
Keywords: business; revival; losses; efficiency; income